Analysis of Rewards and Punishment on the Performance of State-Owned Enterprise Employees in Medan Region - Suwarno, Bambang; Harahap, Arman (International Journal of Science, Technology & Management, 2025)
Motivating workers through the use of rewards and punishments, the management control system places an emphasis on output. Any decent employee will follow the rules set out by their employer and will push for their coworkers to do the same. Finding out whether company rewards and punishments have an effect on employee performance in a State-Owned Enterprise is the main objective of this study. Quantitative studies employ non-probability purposive sampling and associative causality studies. With the aid of SmartPLS, descriptive statistics were applied to 100 questionnaires. All of the study's variables were found to have a positive and statistically significant effect. With a t-statistic value of 4.218, employees believe that the company's performance reviews can positively affect their pay, benefits, and advancement opportunities. The company's punisment motivate employees to perform well in order to avoid pay cuts and promotion delays (t-statistic value 4.861). When workers' expectations regarding company assessments and reward are satisfied, their performance improves (t-statistic value 3.900). Therefore, it is reasonable to assume that, with proper implementation of evaluation and sanctions, staff performance will improve. While punishments are the most powerful incentive for improving performance, this study's original finding is that positive reinforcement in the form of awards can inspire loyalty and good conduct.